Evolution of the EU Approach to Central Asia: from Positive Observer to Geopolitical Player - Ya. V. Leksyutina (Сравнительная политика, 2024)
In recent years and especially after February 2022, there has been a sharp intensification of Brussels’ engagement with Central Asia. The growing interest in Central Asia is due to the EU’s desire to develop an alternative version of infrastructure development and connectivity in the region as opposed to the China’s Belt and Road Initiative, to use the resource potential of the region to reduce dependence on China for green and digital transition strategy, and the region’s transit potential for development transport and energy infrastructure bypassing Russia. The new geopolitical situation and the trends developing in Central Asia are regarded in Brussels as providing a “window of opportunity” to increase the EU’s presence. Moreover, the EU’s policy towards Central Asia starts to be driven by geopolitical interests. Containing Russia, limiting Russia’s and China’s influence in the region, reducing dependence on China are becoming the main goals of Brussels’ policy in the region. The “benevolent indifference” to the region that once characterized the EU is being replaced by Brussels’ desire to become a major geopolitical player in the region. The article provides a retrospective analysis of the EU policy towards Central Asia throughout the entire period of official interaction between the parties. The focus of the article is to trace the evolution of the goals, priorities and interests of the EU in the region, identify the driving forces that determined Brussels’ policy towards the region at different historical stages, and determine the tools used to achieve the goals. The article also describes the largest EU initiatives for the region. The author concludes that in the current geopolitical situation, Central Asia has no independent significance for Brussels: policy towards the region is built through the prism and in accordance with the logic of confrontation with Russia and hedging risks associated with China.